THE TYPOLOGY OF MANIPULATIVE DISCOURSE TACTICS AIMED AT THE IRRATIONAL COMPONENTS OF ADDRESSEE’S INNER WORLD EXPLOITING - Ievgeniia V. Bogatyrova (Вестник Северо-Кавказского федерального университета)
The article deals with the issue of the typology of the manipulative discourse tactics based on the irrational mechanisms of addressee’s world perception exploiting. The systematization of the manipulative tactics is carried out with due consideration of the views presented in theoretical sources as well as of the corpus analysis. All the manipulative tactics pointed out within this work are regarded as the means for the discourse strategies of positive self-presentation and negative presentation of an opponent realization, which we consider the basic discourse strategies of the discourse type in study.